THE SOCIAL REPRESENTATION OF THE CONTEMPORARY FAMILY FROM THE PERSPECTIVE OF DIFFERENCES IN THE LEVEL OF EDUCATION (study conducted in the social and cultural context of the Republic of Moldova) - CAZACU Daniela (Psihologie, 2018)
The family (still) is one of the fundamental values that can contribute to the stability of society. Family psychology and couple psycho-socialists suggest that in the contemporary society the representations of concepts relating to romantic and premarital relationships, marriage, family, or couple life are very diverse and often erroneous. The main variable that is taken into account in this research is the level of education, starting from the premise that in the Republic of Moldova this variable diff erentiates the universe of the family social representation.